Anionic polymer, anion exchange membrane, method and electrolyzed water reactor
By introducing high alkali resistance cationic groups and side chain structures into the polymer framework structure of the anion exchange membrane and forming a crosslinking network structure, the stability of the anion exchange membrane in an alkaline environment is solved, and efficient ion conduction and long-term stable operation are achieved.
Patent Information
- Application Number
- CN202411693609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
The anion exchange membrane in the prior art is prone to degradation in an alkaline environment, resulting in a decrease in ion conductivity, a weakening of mechanical strength and a deterioration of dimensional stability, and lacks high alkali resistance stability.
Into the polymer backbone structure containing fluorine-containing structural units, a high alkali resistance cationic group and a side chain structure providing in-situ polymerization sites are introduced to form an anionic polymer of the polyaryl backbone structure, and a crosslinking network structure is formed by in-situ polymerization.
It improves the alkali resistance and dimensional stability of the anion exchange membrane, maintains high ion conductivity, extends the service life of the equipment, and reduces energy waste and environmental pollution.
Smart Images

Figure CN119529241A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular to an anion polymer, an anion exchange membrane, a method and a water electrolysis reactor. Background Art
[0002] As a key functional membrane material, anion exchange membrane plays an irreplaceable role in electrochemical devices such as water electrolysis for hydrogen production, alkaline fuel cells, flow batteries and electrodialyzers. These devices are widely used in clean energy, environmental protection and chemical production, and are of great significance for promoting sustainable social development. Anion exchange membranes achieve effective separation and regulation of ions in electrolyte solutions by selectively conducting anions, thereby ensuring the efficient and stable operation of electrochemical devices.
[0003] Although anion exchange membranes play an important role in electrochemical devices, anion exchange membranes in the prior art still have many deficiencies in comprehensive performance. Alkali resistance stability is a key indicator to measure the stability of anion exchange membranes in alkaline environments. Anion exchange membranes in the prior art are prone to degradation in alkaline environments, resulting in decreased ion conductivity, weakened mechanical strength, and poor dimensional stability. This alkali resistance instability not only limits the application scope of membrane materials, but also increases the maintenance cost and safety risks of electrochemical devices.
[0004] In summary, the anion exchange membranes in the prior art have many deficiencies in terms of ion conductivity, chemical stability, etc., especially in terms of alkali resistance stability, which needs to be improved urgently. Therefore, the development of a new anion exchange membrane material that can maintain high ion conductivity and significantly improve alkali resistance stability and dimensional stability has become an urgent need for current research. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides an anion polymer, anion exchange membrane, method and water electrolysis reactor, which introduces highly alkali-resistant cationic groups and side chain structures that provide in-situ polymerization sites into the polymer skeleton structure containing fluorine-containing structural units, thereby maintaining the high ion conductivity of the anion exchange membrane while improving the alkali resistance stability and dimensional stability, thereby achieving comprehensive optimization and improvement of the anion exchange membrane performance.
[0006] To achieve the above object, the present invention provides the following technical solution: an anionic polymer, wherein the anionic polymer is a polyaryl skeleton structure, and the polyaryl skeleton structure is connected with a highly alkali-resistant cationic group and a fluorine-containing side chain structure, and the specific structural formula is as follows:
[0007] Wherein, A is an aromatic group, x is 50-99, and q is 0-10.
[0008] Furthermore, the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
[0009] Furthermore, the highly alkali-resistant cationic group is provided by 3-quinuclidinone hydrochloride or 3-quinuclidinone.
[0010] Furthermore, the fluorine-containing side chain structure is provided by trifluoromethyl p-(vinyl) phenethyl ketone.
[0011] The present invention provides a method for preparing anionic polymers, the specific steps of which are as follows: 100 parts of an aromatic compound, x parts of 3-quinuclidinone hydrochloride or 3-quinuclidinone and 100-x parts of trifluoromethyl p-(vinyl)phenylethyl ketone are mixed and dissolved in a solvent, reacted under the catalysis of Lewis acid at 0° C., and unreacted reactants are removed to obtain an intermediate polymer; Under alkaline conditions, 100 to 1000 parts of methyl iodide are added to 100 parts of the intermediate polymer solution to react and obtain an anionic polymer.
[0012] Furthermore, the structural formula of the anionic polymer is as follows:
[0013] Wherein, A is an aromatic group, and the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, 9,9-dimethylfluorene, x is 50-99, and q is 0-10.
[0014] The present invention also provides an anion exchange membrane, which is prepared by using an anion polymer, and the structural formula of the anion polymer is as follows:
[0015] Wherein, A is an aromatic group, and the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, 9,9-dimethylfluorene, x is 50-99, and q is 0-10.
[0016] The present invention also provides a method for preparing an anion exchange membrane, the specific steps of which are as follows: Add the anionic polymer into the solvent and fully dissolve it to obtain an anionic polymer solution with a mass fraction of 1% to 50%: The anion polymer solution is poured into a mold, heated to 50-120°C and dried for 30 min-12 h, and in-situ polymerized to obtain an anion exchange membrane with a cross-linked network structure.
[0017] Furthermore, the thickness of the anion exchange membrane is 10 μm to 150 μm.
[0018] The present invention also provides a water electrolysis reactor, comprising the anion exchange membrane.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides an anionic polymer, which adopts a polyaryl skeleton structure. The polyaryl skeleton structure provides good mechanical properties and thermal stability, and introduces a highly alkali-resistant cationic group and a fluorine-containing side chain structure into the polyaryl skeleton structure. The highly alkali-resistant cationic group can remain stable in a highly alkaline environment, and the fluorine-containing side chain structure not only enhances the alkali resistance of the polymer, but also provides an in-situ polymerization site, which is helpful to form a cross-linked network structure.
[0020] The anion exchange membrane prepared by the above anion polymer has high ion conductivity due to the introduction of polyaryl skeleton structure and cationic groups; the highly alkali-resistant cationic groups and fluorinated side chain structures enable the membrane to operate stably for a long time in a highly alkaline environment. The cross-linked network structure formed by in-situ polymerization enhances the dimensional stability of the membrane and avoids the performance degradation caused by dimensional changes during use. The present invention not only maintains the high ion conductivity of the anion exchange membrane, but also significantly improves its alkali resistance stability and dimensional stability, thereby achieving comprehensive optimization and improvement of the performance of the anion exchange membrane.
[0021] The anion exchange membrane of the present invention is applied to a water electrolysis reactor. Since the anion exchange membrane has excellent ion conductivity and alkali resistance stability, the efficiency of the water electrolysis reactor is significantly improved. The improvement of the alkali resistance stability and dimensional stability of the anion exchange membrane of the present invention enables the water electrolysis reactor to operate stably for a long time in a harsh environment, thereby extending the service life of the equipment. The present invention reduces energy waste and environmental pollution by optimizing the performance of the anion exchange membrane, and has broad application prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The ionic conductivity data of the anion exchange membrane of the present invention at 80°C; Figure 2 Data graph of ion conductivity retention rate of anion exchange membrane of the present invention after alkali immersion for 2000 hours. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0025] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0026] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0027] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0028] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0029] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0030] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0031] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0032] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0033] The present invention provides an anionic polymer, wherein the polymer selects a polyaryl skeleton structure, and introduces a cationic group with high alkali resistance and a side chain structure with a fluorine-containing structural unit into the polyaryl skeleton structure. The specific structural formula is as follows:
[0034] Preferably, A is an aryl group, and the aryl group may be one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene; x is 50-99, and q is 0-10.
[0035] The present invention provides a method for preparing the above-mentioned anionic polymer, and the specific steps are as follows: (1) 100 parts of an aromatic compound, x parts of 3-quinuclidine hydrochloride or 3-quinuclidine and 100-x parts of trifluoromethyl p-(vinyl)phenylethyl ketone are mixed and dissolved in a solvent, reacted under the catalysis of Lewis acid at 0°C, and unreacted reactants are removed to obtain an intermediate polymer; Among them, 3-quinuclidine hydrochloride or 3-quinuclidine provides a cationic group with high alkaline resistance for the polymer, and trifluoromethyl p-(vinyl)phenylethyl ketone provides a fluorine-containing structural unit for the polymer, providing a cross-linking reaction site for subsequent in-situ polymerization.
[0036] (2) Under alkaline conditions, iodomethane is added to the intermediate polymer solution to react to obtain an anionic polymer. The anionic polymer is an anion of I - of functionalized polymers.
[0037] Preferably, the addition ratio of the intermediate polymer to methyl iodide is 100 parts: 100 parts to 1000 parts.
[0038] The present invention also provides an anion exchange membrane, which is prepared by using the anion polymer, and the specific steps are as follows: (1) Add the anionic polymer into the solvent and fully dissolve it to obtain an anionic polymer solution with a mass fraction of 1% to 50%: (2) pouring the anionic polymer solution into a mold, heating it to 50-120°C and drying it for 30 min-12 h, and in-situ polymerizing it to obtain an anion exchange membrane with a cross-linked network structure; Preferably, the thickness of the anion exchange membrane is 10 μm to 150 μm; (3) Immersing the anion exchange membrane in different ion exchange solutions to obtain anion exchange membranes of desired anions.
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] Example 1 A is p-terphenyl, x=80, q=0 A method for preparing an in-situ cross-linked anion exchange membrane with high alkali resistance stability, the specific steps are as follows: (1) Weigh 10.0 mmol of p-terphenyl into a 100 mL three-necked flask, add 8.0 mmol of 3-quinuclidine hydrochloride and 2.0 mmol of trifluoromethyl p-(vinyl)phenylethyl ketone, and add 10 mL of dichloromethane to dissolve the reactants. Add 12 mL of trifluoromethanesulfonic acid and 1 mL of trifluoroacetic acid at 0 °C and stir mechanically for 12 hours. Pour the viscous purple product into a 1M 2 CO 3 The product was immersed in the solution at room temperature for 24 hours, filtered to obtain a white solid product, washed thoroughly with deionized water and dried to obtain an intermediate polymer with the following structural formula:
[0041] (2) Weigh 1.2 g of the intermediate polymer in a 100 mL single-necked flask, add 15 mL of dimethyl sulfoxide, and add 150 μL of trifluoroacetic acid to promote the dissolution of the polymer. After the polymer is completely dissolved, add 0.36 g of potassium carbonate and 300 μL of iodomethane. React at room temperature for 48 h. Pour the reaction product into ethyl acetate to precipitate a yellow precipitate. Wash it several times with ethyl acetate, then wash it with water and dry it to obtain an anion of I - The functionalized polymer has the following structural formula:
[0042] (4) Weigh 1g of the functionalized polymer, add 50mL of dimethyl sulfoxide, and pour it into the groove of a flat glass plate after it is fully dissolved. Dry it at 80°C for 48 hours to form a film, and at the same time, form a cross-linked network structure in situ. After the film is peeled off the glass plate, it is immersed in a 1M KOH solution and ion exchange is performed at room temperature for 48 hours to obtain an anion of OH - The anion exchange membrane has the following structural formula:
[0043] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 168 mS / cm at 80°C; Figure 2 As shown in the figure, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali immersion for 2000 hours is 97.8%. The cross-linked structure significantly improves the ion conductivity and alkali resistance stability of the anion exchange membrane.
[0044] Example 2 A is p-terphenyl, x=50, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows: .
[0045] Example 3 A is p-terphenyl, x=99, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows: .
[0046] Example 4 A is p-terphenyl, x=80, q=2 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows: .
[0047] Example 5 A is p-terphenyl, x=80, q=10 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows: .
[0048] Example 6 A is biphenyl, x=80, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0049] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 170 mS / cm at 80°C; Figure 2 As shown, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali leaching for 2000 hours was 97.0%.
[0050] Example 7 A is 80% p-terphenyl + 20% m-terphenyl, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane with the following structural formula: .
[0051] Example 8 A is 80% p-terphenyl + 20% diphenylethane, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane. .
[0052] Example 9 A is 90% p-terphenyl + 10% dimethylfluorene, x=80, q=0 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane with the following structural formula: .
[0053] Comparative Example 1 A is p-terphenyl, x=100, q=0 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0054] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the anion exchange membrane obtained in this comparative example has an ionic conductivity of 142 mS / cm at 80°C; Figure 2 As shown, the ion conductivity retention rate of the anion exchange membrane obtained in this comparative example after 2000 hours of alkaline leaching is 94.9%. Compared with Example 1, the ion conductivity of Comparative Example 1 (see Figure 1 ) and alkali stability (see Figure 2 ) were significantly reduced, indicating that the cross-linked structure significantly improved the ionic conductivity and alkali stability of the anion exchange membrane.
Claims
1. An anionic polymer, characterized in that The anionic polymer is a polyaryl skeleton structure, to which a highly alkali-resistant cationic group and a fluorine-containing side chain structure are connected, and the structural formula is as follows: Wherein, A is an aromatic group, x is 50-99, and q is 0-10.
2. An anionic polymer according to claim 1, characterized in that The aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
3. An anionic polymer according to claim 1, characterized in that The highly alkali-resistant cationic group is provided by 3-quinuclidinone hydrochloride or 3-quinuclidinone.
4. An anionic polymer according to claim 1, characterized in that The fluorine-containing side chain structure is provided by trifluoromethyl p-(vinyl)phenylethyl ketone.
5. A method for preparing anionic polymers, characterized in that: The specific steps are as follows: 100 parts of an aromatic compound, x parts of 3-quinuclidinone hydrochloride or 3-quinuclidinone and 100-x parts of trifluoromethyl p-(vinyl)phenylethyl ketone are mixed and dissolved in a solvent, reacted under the catalysis of Lewis acid at 0° C., and unreacted reactants are removed to obtain an intermediate polymer; Under alkaline conditions, 100 to 1000 parts of methyl iodide are added to 100 parts of the intermediate polymer solution to react and obtain an anionic polymer.
6. The method for preparing an anionic polymer according to claim 5, characterized in that: The structural formula of the anionic polymer is as follows: Wherein, A is an aromatic group, and the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, 9,9-dimethylfluorene, x is 50-99, and q is 0-10.
7. An anion exchange membrane, characterized in that: It is prepared by using anionic polymer, and the structural formula of the anionic polymer is as follows: Wherein, A is an aromatic group, and the aromatic group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, 9,9-dimethylfluorene, x is 50-99, and q is 0-10.
8. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The specific steps are as follows: Add the anionic polymer into the solvent and fully dissolve it to obtain an anionic polymer solution with a mass fraction of 1% to 50%: The anion polymer solution is poured into a mold, heated to 50-120°C and dried for 30 min-12 h, and in-situ polymerized to obtain an anion exchange membrane with a cross-linked network structure.
9. The method for preparing an anion exchange membrane according to claim 8, characterized in that: The thickness of the anion exchange membrane is 10 μm to 150 μm.
10. A water electrolysis reactor, characterized in that: Comprising the anion exchange membrane according to claim 7.